(untitled) (National Administration Journal, 2021)
Despite the existence of technological transfer (TT) reseach, there are very few articles related to leaders’ managerial or technical skills and there are none in emerging countries. Therefore, this article analyses the case of Mexico and focuses particularly on predominating skills in the profile of agents in technological transfer offices in Mexican universities. Through a multifactorial statistical analysis, eight components were identified, containing eight constructs by 79,4%. As a result, the identification of the transfer agent profile is shown.